Noncompete agreements in employment contracts - Kurt Lavetti (IZA World of Labor, 2021)
Labor market institutions that may weaken workers' bargaining leverage have received increased scrutiny in recent years. One example is noncompete agreements, which prevent workers from freely moving across employers, potentially weakening earnings growth. New data sources and empirical evidence have led policymakers to consider sharp restrictions on their use, especially among lower-income workers. These restrictions take many different forms, each of which has unique tradeoffs between the desire to protect workers while allowing firms to use noncompetes in cases where they may create social value.
Keywords: J30; J41; J42; J68; K31; 330; noncompete agreements; employment law; wages; job mobility